2022
DOI: 10.1080/10717544.2022.2059124
|View full text |Cite|
|
Sign up to set email alerts
|

Manganese-containing polydopamine nanoparticles as theranostic agents for magnetic resonance imaging and photothermal/chemodynamic combined ferroptosis therapy treating gastric cancer

Abstract: Gastric cancer (GC) is a serious disease with high morbidity and mortality rates worldwide. Chemotherapy plays a key role in GC treatment, while inevitable drug resistance and systematic side effects hinder its clinical application. Fenton chemistry-based chemodynamic therapy (CDT) has been used as a strategy for cancer ferroptosis, and the CDT efficiency could be enhanced by photothermal therapy (PTT). With the trend of treatment and diagnosis integration, the combination of magnetic resonance imaging (MRI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…However, their longitudinal relaxivity (r1) is relatively low (<9.0 m m −1 s −1 ), [ 14 ] and the sensitivity of MRI frequently depends on the high relaxivity values of contrast agents. [ 15 ] Wu et al constructed a dotted core‐shell type FeGd‐HN nanoparticle with super high r1 value (21.0 ± 1.3 m m −1 s −1 , B 0 = 7.0 T) and very low r2/r1 ratio for high contrast T 1 ‐weighted MRI of subcutaneous xenografts tumors, [ 16 ] but the accurate identification of small PM nodules continues to be a challenge. Previous studies have shown that compared with passive target delivery, decoration with active targeting ligands (including cRGD, RGD, or RGD2), which can actively identify specific receptors on the target cell, is efficient.…”
Section: Introductionmentioning
confidence: 99%
“…However, their longitudinal relaxivity (r1) is relatively low (<9.0 m m −1 s −1 ), [ 14 ] and the sensitivity of MRI frequently depends on the high relaxivity values of contrast agents. [ 15 ] Wu et al constructed a dotted core‐shell type FeGd‐HN nanoparticle with super high r1 value (21.0 ± 1.3 m m −1 s −1 , B 0 = 7.0 T) and very low r2/r1 ratio for high contrast T 1 ‐weighted MRI of subcutaneous xenografts tumors, [ 16 ] but the accurate identification of small PM nodules continues to be a challenge. Previous studies have shown that compared with passive target delivery, decoration with active targeting ligands (including cRGD, RGD, or RGD2), which can actively identify specific receptors on the target cell, is efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ce-based nanocomposites show good GSH consumption and radical generation for chemodynamic therapy, they still need other treatment (e.g., photothermal therapy) methods to enhance the therapeutic effect. Associated with the PTT capability, PTT/CDT combined therapy can be realized because the PTT reagent not only kills cancer cells by elevating the temperature but also accelerates the production of ROS in CDT . Therefore, endowing Ce with photothermal agents is beneficial to enhance their CDT efficacy …”
Section: Introductionmentioning
confidence: 99%
“…PTT capability, PTT/CDT combined therapy can be realized because the PTT reagent not only kills cancer cells by elevating the temperature but also accelerates the production of ROS in CDT. 15 Therefore, endowing Ce with photothermal agents is beneficial to enhance their CDT efficacy. 16 Photothermal therapy (PTT) is a hot topic in recent years in the field of biomedical and materials science study.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ferroptosis is a newly discovered form of programmed cell death characterized by iron-dependent lethal accumulation of lipid peroxides (lipid reactive oxygen species or lipid ROS) that was recently identified as one of the mechanisms of cancer cell death in several cancers, including liver cancer, kidney cancer, bone cancer, and lung cancer ( Chen et al, 2022 ; Peng et al, 2023 ). Ferroptosis occurs when the levels of lipid ROS exceed the cellular antioxidative threshold and oxidative stress overload is induced in cells ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%